MACHIAVELLANISM IN EKA KURNIAWAN’S NOVEL LELAKI HARIMAU - Sonya, Trisya; Anayati, Wan; Pratiwy, Devi (JOURNAL OF LANGUAGE, 2024)
This research examines Machiavellianism in Eka Kurniawan’s novel Lelaki Harimau (Man Tiger), investigating how characters navigate power dynamics and ethical dilemmas in rural Indonesia. Drawing on Niccolò Machiavelli’s The Prince (1532), the study analyzes how characters employ cunning, manipulation, and strategic thinking to achieve personal goals. Utilizing textual, thematic, and interpretative analysis, the study dissects the novel’s narrative structure, character development, and thematic concerns related to Machiavellianism. Key passages reveal that characters, notably Margio, exemplify Machiavellian traits through concealing intentions, manipulating perceptions, and rationalizing morally ambiguous actions. The novel portrays a complex interplay of power dynamics, personal ambition, and cultural influences, shedding light on human capacity for deception and pursuit of power. This research deepens understanding of Machiavellianism in Southeast Asian literature, illuminating its role in exploring universal themes of power, morality, and human nature within an Indonesian context. By contextualizing Machiavellian behavior, the study enriches discussions on literature’s reflection of societal norms and ethical dilemmas, offering a nuanced perspective on Kurniawan’s portrayal of complex moral landscapes in contemporary fiction.